Examining financial well-being among students: Islamic social finance and theory of planned behavior approach - Norizan, Siti Noraisyah Binti; Abu Bakar, Nashirah Binti; Iqbal, Muhammad Saeed; Idris, Izzyan Binti Mohd (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study explores the interconnections between financial attitudes, subjective norm, perceived behavioral control, and Islamic social finance toward financial well-being. It examines how these factors contribute to financial stability, particularly within the context of Islamic finance.Methodology – This study used a quantitative approach, and data analysis was conducted using SPSS 30. This study applied regression, correlation, and factor analyses to examine the relationships between the variables. Data were validated through reliability testing, normality assessments, and evaluations of construct validity to ensure methodological rigor and accuracy.Findings – The results showed a significant relationship between attitudes, subjective norm, strong perceived behavioral control, and Islamic social finance toward financial well-being. These findings validated our hypotheses.Implications – This study provides valuable insights for policymakers, financial institutions, and educators by highlighting the importance of fostering positive financial attitudes, enhancing financial self-efficacy, and promoting Islamic social finance practices. These findings can guide strategies to improve financial well-being across diverse socioeconomic groups.Originality – This study contributes to the literature by providing a comprehensive analysis of how the theory of planned behavior and Islamic social finance collectively influence financial well-being.